The Determinants and Interdepence of Entry and Exit - Shen, Yaxiong (Université d'Ottawa | University of Ottawa, 2005)
Entry and exit play a crucial role in microeconomic models of market structure and performance. This paper reviews empirical studies of the determinants and interdependence of entry and exit. It summarizes and compares a broad range of empirical results f